Innovative devices for advanced heart failure. (May 2015) - Grinstein, Jonathan; Burkhoff, Daniel
<x xml:space="preserve">Abstract</x> Purpose of review Despite improvements in medical and device therapies for the treatment of heart failure, the incidence and prevalence of heart failure continue to increase. Given the relative stagnation in new pharmacologic therapies, considerable attention has been given in recent years to device therapies to supplement care in patients with advanced heart failure. Recent successful clinical trial results with an angiotensin–neprilysin inhibitor are not expected to change this situation significantly; the drug has been shown to delay, not eliminate, the progression of heart failure. This review focuses on the technologies that are currently in development for the treatment of advanced heart failure. Recent findings Novel devices that involve electrical, neurohormonal or structural remodeling of the heart that can be inserted either percutaneously or with a minimally invasive surgery are currently at various stages of clinical development. All, however, have shown promising clinical results in preclinical and early clinical studies. Summary Novel device therapies for advanced heart failure continue to show promising clinical results. Randomized controlled trials are still needed to better evaluate their efficacy. Nevertheless, it can be anticipated that at least several of these devices will be among the armamentarium of treatment options for advanced heart failure in the future.